UNVEILING THE LEVEL OF DIGITAL POVERTY: A PHENOMENOLOGICAL STUDY ON DIGITAL POVERTY AMONG YOUTH IN DENPASAR CITY - Komang Ema Marsitadewi; Victorius Adventius Hamel (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
The advancement of technology today should be accessible to everyone and all segments of society, especially those in their teenage years and productive age. This research explores and seeks to understand how urban adolescents from low-income families perceive and experience digital poverty. Using a qualitative approach, in-depth interviews were conducted with adolescents from low-income families who are scholarship recipients. The main goal of this research is to uncover their perspectives on access to digital devices, availability of internet connections, and how they utilize the technology. The findings from the interviews indicate that most informants have limited access to technology, with some only owning mobile phones without laptops or computers, and they often rely on mobile data or public or neighbors' Wi-Fi networks. Nevertheless, some informants did not feel significantly left behind in terms of technological access, although they were aware of the disparity when comparing themselves to more affluent peers. The study also found that the use of digital technology among low-income adolescents is primarily focused on educational purposes, despite the limitations of the technological resources available to them. Given these constraints, this research suggests the importance of increasing equitable digital access and developing digital skills training programs that can help adolescents from low-income families avoid falling further behind in the rapidly advancing digital era.